ANALISIS EMPOWERMENT DAN EMOTIONAL CAPITAL PADA STAF PENDIDIK DI FAKULTAS KEPERAWATAN DAN KEBIDANAN UNUSA - Eppy Setiyowati Setiyowati (Universitas Nahdlatul Ulama Surabaya, 2017)
Development of resources for organizations, especially educational organizations, namely the lecturer is essentially an investment. Educational staff activity trends for 3 years have decreased by 13%, this is one of the problems for a college institution in emotional capital in a lecturer. The purpose of this research is to analyze empowerment and emotional capital in the staff of educator in Unusa. The research design was survey with cross sectional approach. The population is all lecturers in the Faculty of Nursing and Midwifery as many as 73 people, Sample is a permanent lecturer and has had the certificate of teaching as many as 16 people, the sampling is done through simple random sampling. Dependent variable is empowerment and independent variable is emotional capital. The result of this research showed that spearman rank analysis got significance level p = 0,005 <α = 0,05 meaning Ho rejected means there is relationship between empowerment with Emotional capital. The conclusion of this study shows that the dimension of emotional capital in the sub variable self awarness has a very important meaning for the management of human resources. It is recommended for organizers of the organization especially in the field of human resources management to give attention to the self awarness of the employees.